Importance of Angomonas deanei KAP4 for kDNA arrangement, cell division and maintenance of the host-bacterium relationship - Camila Silva Gonçalves (Nature Portfolio, 2021)
Abstract Angomonas deanei coevolves in a mutualistic relationship with a symbiotic bacterium that divides in synchronicity with other host cell structures. Trypanosomatid mitochondrial DNA is contained in the kinetoplast and is composed of thousands of interlocked DNA circles (kDNA). The arrangement of kDNA is related to the presence of histone-like proteins, known as KAPs (kinetoplast-associated proteins), that neutralize the negatively charged kDNA, thereby affecting the activity of mitochondrial enzymes involved in replication, transcription and repair. In this study, CRISPR-Cas9 was used to delete both alleles of the A. deanei KAP4 gene. Gene-deficient mutants exhibited high compaction of the kDNA network and displayed atypical phenotypes, such as the appearance of a filamentous symbionts, cells containing two nuclei and one kinetoplast, and division blocks. Treatment with cisplatin and UV showed that Δkap4 null mutants were not more sensitive to DNA damage and repair than wild-type cells. Notably, lesions caused by these genotoxic agents in the mitochondrial DNA could be repaired, suggesting that the kDNA in the kinetoplast of trypanosomatids has unique repair mechanisms. Taken together, our data indicate that although KAP4 is not an essential protein, it plays important roles in kDNA arrangement and replication, as well as in the maintenance of symbiosis.